An Overview on Fecal Microbiota Transplantation and it’s Therapeutic Applications on Dysbiosis: As Golden Juice - Kumar, Prevesh (Asian Journal of Pharmaceutics (AJP), 2022)
In current scenario, the investigational studies in pathology fields focus on those microbiotas which can produce sever disorders and also terminate the microbiota colonies that cause or which altered and arise with some diseasecausing agents. Fecal microbiota transplantation (FMT) may alter the acceptors gut microbiota and maintain the composition in normal range, which helps to give beneficial pharmacological effects in gastrointestinal tract (GIT) related disease as well as, extra-GIT disorders. Alteration in microbiomes have given appropriate clinical perceptions in both gut and oral disorders. FMT re-established miscellaneous bacterial profile to GIT. The study was focused on the evaluation of efficacy of this method to treat various infections arises with Clostridium difficile bacteria. From the various studies, it may be hypothesized that the FMT reflects that it has potency to treat the C. difficile infections and achieved success rate in between 80 and 100%. Fecal microbiota can be transplant by both either antegrade or retrograde routes. The history of FMT belongs to the 4th century and comes in enforcement in 2013 after approving by the USFDA.